How Blackwater Takes Uncle Sam for a Ride - and Why He Likes It. A Model of Moral Hazard and Limited Commitment - Matthias Fahn; Tahmina Sadat Hadjer (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
Private Military and Security Companies (PMSCs) have been gaining increasing media and scholarly attention particularly due to their indispensable role in the wars in Afghanistan 2001 and Iraq 2003. Nevertheless, theoretical insights into the agency problems inherent when hiring PMSCs and how to optimally incentivize them are scarce. We study the complex relationship between intervening state, host state, and PMSC, taking into account the diverging interests of all involved parties as well as potential agency problems. We develop a theoretical model to characterize a state's optimal choice whether to perform a task associated with an intervening mission itself, hire a PMSC and optimally design the contract, or completely abstain from it. We find that it might be optimal to hire PMSCs even if they are expected to do a worse job than the intervening state would do itself. This outcome is especially problematic for the host state, which prefers associated tasks to be done as good and carefully as possible. Furthermore, the often-heard call for transparency regarding agreements with PMSCs can lead to a situation where the latter's performance gets even worse - namely because the ability to implicit reward PMSCs for a good performance in the past is reduced.
urn:nbn:de:bvb:19-epub-20832-9
Keywords: C72; C73; F51; F53; 330; International Conflicts; Private Military and Security Companies; Moral Hazard; Relational Contracts